Influence of sex on the incidence of potential coronary artery disease and long-term outcomes in asymptomatic patients with diabetes mellitus. (April 2020) - Sato, Chisato; Wakabayashi, Kohei; Ikeda, Naoko; Honda, Yuki; Sato, Ken; Suzuki, Toshiaki; Shibata, Keita; Tanno, Kaoru
Abstract: Background: Diabetic patients often have coronary artery disease (CAD) without symptoms. It is known that females tend to have silent or less chest pain and worse prognoses when they develop acute coronary syndrome. Thus, sex differences may impact long-term outcomes in diabetes mellitus (DM) patients with silent myocardial ischemia (SMI). The present study aimed to assess the influence of sex on long-term outcomes in DM patients with SMI. Methods: A total of 461 consecutive asymptomatic and self-sufficient DM patients seen at our hospital from 2011 to 2017 were prospectively reviewed. Patients underwent an ergometer exercise test. When the exercise test was positive or the patient could not achieve 90% of their target heart rate, coronary angiography was performed. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCEs), including death, non-fatal myocardial infarction, and stroke. Results: SMI was diagnosed in 81 patients. The median follow-up duration from diagnosis was 35 (15–57) months. The incidence of SMI was similar in females and males [34/170 (20%) vs. 47/291 (16.2%), p = 0.36]. Enrolled patients were divided into four groups according to sex and the presence/absence of SMI. Female patients with SMI showed worse clinical outcomes. After adjustment for age and coronary risk factors, female SMI was independently associated with MACCEs [hazard ratio 2.59, 95% confidence interval 1.07–5.68, p = 0.024], while male SMI was not. Conclusions: Female SMI was associated with worse long-term outcomes in DM patients. Early diagnosis of potential SMI and appropriate care are required in female DM patients. (UMIN000038340).